BILINGUISM IN A MODERN SECONDARY SCHOOL IN A MULTICULTURAL SOCIETY - Malokhat Turavayevna Yunusova (Web of Journals Publishing, 2024)
The article discusses the significance of studying aspects of bilingualism in a modern secondary school in a multicultural society. An analysis of the problem of bilingualism in schools was carried out. The activities of the school are considered as a social institution that shapes not people in general, but people in and for a specific society. Various definitions of the terms “multicultural society” and “multilingual society” in the modern world and their differences are considered. The current linguistic situation in Uzbekistan is summarized.
Keywords: multicultural society, transnational society, multilingual society, bilingualism, bilingual education, bilingual schools, bilingual education.